Planting and Propagation of Snapdragons in Florida - Heqiang Huo; Jianjun Chen (EDIS)
Snapdragons are a common plant in Florida landscapes and are one of the top ten fresh-cut flowers in the nation. This 5-page publication, written by Heqiang Huo and Jianjun Chen, explores the planting and propagation of snapdragons in Florida landscapes. Published by the UF/IFAS Department of Environmental Horticulture, January 2018. http://edis.ifas.ufl.edu/ep549